Acceleration profile of an acrobatic act during training and shows using wearable technology - Barker, L.; Burnstein, B.; Mercer, J. (Sports Biomechanics, 2020)
The purpose of this study was to describe the mechanical characteristics of a trampoline circus act and its individual tracks performed in training and shows using a tri-axial accelerometer. A track is an artist`s specific role within a choreographed act. Seven male acrobats performed their trampoline act during training and shows while wearing a triaxial accelerometer and reported ratings of perceived exertion (RPE) after each trial. Average acceleration (AVG), root mean square (RMS), root mean to the fourth (RM4), time spent in specific acceleration ranges and RPE were measured/recorded from training and show acts. Paired t-tests compared dependent variables between training and show. Acceleration AVG, RMS and RM4 were significantly higher (p < 0.05) in training than show. RPE was significantly higher (p < 0.05) in show than training. No significant differences existed in time spent in any of the acceleration ranges between training and show. GPS devices have been used to manage workloads in field sports but are inoperable in theatres. But, inertial measurements may be an effective alternative to describe mechanical demands in theatre or arena environments. Wearable technology may be useful to coaches to improve understanding of track demands to manage artist workloads.